Increase Safety of Traffic Control on the Minor Railway-Tracks - Jan Slezak; Juraj Spalek (Communications - Scientific letters of the University of Zilina, 2011)
The paper aims at detecting the existing safety risks on the minor railway-tracks being operated in accordance with the provision CD-D3 of the Czech Railways, and at providing the solutions and technologies suitable for the mentioned minor railway-tracks. These tracks are currently equipped with out of date safety related systems monitoring the railway, whose operation depends purely on human factor. The latest railway accidents were reported just on these low traffic frequency tracks.